Dynamics Behavior of a Stochastic Predator-Prey Model with Stage Structure for Predator and Lévy Jumps (Journal of Nonlinear Modeling and Analysis, 2024)
In order to study the effects of external environmental noise on theinteraction dynamics between predator and prey populations, in this paper, wedevelop a predator-prey model with the stage structure for predator and Lévynoise. By constructing an appropriate Lyapunov function, we first prove thatthe proposed model exists the uniqueness of global positive solution. Then,we analyze the persistence and extinction of the proposed model. Finally, weperform some numerical simulations to verify the correctness of the theoreticalresults.